Postzygotic mosaicism in basal cell naevus syndrome. (6th June 2017) - Reinders, M.G.H.C.; Boersma, H.J.; Leter, E.M.; Vreeburg, M.; Paulussen, A.D.C.; Arits, A.H.M.M.; Roemen, G.M.J.M.; Speel, E.J.M.; Steijlen, P.M.; van Geel, M.; Mosterd, K.
Summary: Basal cell naevus syndrome (BCNS) is an autosomal dominant disorder most commonly caused by a germline mutation in the Drosophila homologue of patched‐1 gene ( PTCH1 ). Here we describe a patient with clinical signs of BCNS, caused by postzygotic mosaicism of a PTCH1 mutation. We performed restriction fragment length polymorphism analysis and Droplet Digital polymerase chain reaction to determine the degree of mosaicism in different tissues of this patient. Our case shows that a relatively low‐grade mosaicism can lead to clinical signs reminiscent of those caused by a germline mutation. This finding has important implications for genetic counselling and therefore is pivotal to recognize for dermatologists, as well as for clinical geneticists and clinical laboratory geneticists. Abstract : What's already known about this topic? Basal cell naevus syndrome (BCNS) is generally caused by a germline mutation in the patched‐1 gene ( PTCH1 ). Genetic mosaicism in BCNS has been described. What does this study add? A low‐grade postzygotic mosaicism of a PTCH1 mutation can cause a clinical presentation fulfilling the diagnostic criteria of BCNS. It is important to determine the degree of mosaicism as accurately as possible with a quantitative technique, for example Droplet Digital polymerase chain reaction, to provide adequate genetic counselling. Linked Comment:  Happle. Br J Dermatol 2017;177 :20–21